Integrating the Philosophy of Batik Pacitan in Science Learning Based on Islamic Values to Build Harmonious and Tolerant Character - Wahyuningsih, Diah (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
This study investigates the integration of Pacitan batik philosophy into science learning based on Islamic values to develop students’ harmonious and tolerant character. The object of the research is the philosophical meanings contained in Batik Pacitan motifs that symbolize balance, patience, and harmony with nature. The study aims to identify how these local wisdom values can enrich science learning and promote ethical and character-based education. The research uses a qualitative descriptive method through literature review and interview. The results reveal that integrating Pacitan batik philosophy into science learning fosters moral awareness, environmental empathy, and appreciation of diversity. The discussion emphasizes that Islamic-based contextual science education can harmonize cognitive understanding with ethical and spiritual values. The study concludes that incorporating local wisdom into science education strengthens students’ character and supports global peace-oriented learning.